Prevalência de disfunção velofaríngea e fatores relacionados em pacientes com fissura palatina no estado de Sergipe - Santana, Maria Tereza Maynard (2019)
Introduction: Velopharyngeal Dysfunction (VD) is a negative consequence of palatoplasty surgery in patients with cleft palate and causes significant changes in communication skills. It is characterized with hypernasality, nasal air leak during speech, absence of intraoral pressure and compensatory joint (CA). With palatoplasty surgery, the patient is expected to acquire the integrity and dynamics of the velopharyngeal sphincter. However, in some patients this mechanism remains deficient. Objectives: 1) to analyze and determine the prevalence of VD, 2) to analyze related factors, 3) to relate data to sociodemographic, clinical and speech-language factors in patients with cleft palate after primary palatoplasty surgery in a service in the state of Sergipe (Brazil). ). Methods: This was a cross-sectional study in which the Perceptual Speech Assessment was performed in 80 patients after primary palatoplasty, with at least 6 months after palatoplasty, both genders, followed at the single center. of the State of Sergipe from 2015 to 2017. For data analysis, descriptive statistics was performed using absolute and relative frequencies, trend, central and dispersion measures. Results: 81.3% of patients with altered velopharyngeal mechanism. Regarding related factors, the highest prevalence was mild or mild to moderate air emission; moderate, moderate to severe and severe hypernasality and with a large majority of patients. Regarding sociodemographic variables, among men, 83.7% had VD, while the rate was 78.4% in women. The age groups most affected by VD were children up to 9 years old, followed by adults over 20 years old. As for the other scores; The most prevalent level of education was that of people who had completed the second degree; the most prevalent marital status was single and family income up to R $ 1000. Regarding clinical variables, the type of cleft with the highest rate was transforamen and most patients underwent primary palatoplasty surgery up to 5 years. Regarding the speech-language variables, most patients underwent speech therapy at their own service after primary palatoplasty and obtained moderate / severe intelligibility. Thus, VD has a great impact on the service and it is necessary to rethink the speech therapy intervention protocol. Conclusion: It is concluded from the results obtained that the prevalence of VD in patients with palatine clefts is high; The degree of hypernasality, nasal air leakage and CAs were more severe in patients with VD. Regarding the variables analyzed, hypernasality is more prevalent in patients with VD.